The Effect of Promotion, Price and Service Quality on Tokopedia Online Shopping Repurchase Decisions - Febrianel Sagala (Fakultas Bisnis, 2022)
This study was conducted to find out the influence of promotion, price, and service quality on the decision to repurchase Tokopedia online shopping at the Skincare Tool Shop. This study uses a survey method that is distributing questionnaires with 100 respondents who are Skincare Tool Shop customers. Data processing is help of the SPSS 28.0 program. By using a quantitative research model, namely the acquisition of data in the form of numbers. The data test was carried out using a validity test technique seen from the r count and Croncbach's Aplha as the reliability test. To prove and test the research hypothesis using multiple linear regression analysis. The results of data processing obtained multiple linear equations, with the formula Y = 3.191 + 0.191Xâ‚ + 0.203Xâ‚‚ + 0.539Xâ‚ƒ meaning that each promotion variable increases or decreases by 1, the effect of repurchase decisions increases or decreases by 0.191 points and each price variable increases or decreases by 1 point, then the repurchase decision will increase or decrease by 0.203 points and each service quality variable increases or decreases by 1 point, the effect of repurchase decisions increases or decreases by 0.539 points. From the coefficient of determination of promotion, price and quality of service simultaneously have a large effect of 61.1% on the variable of repurchasing decisions. The hypothesis test results of the acquisition of the promotion tcount of 2.106 tcount of the price variable of 1,992 tcount of the service quality variable of 6.204. Judging from the table of degree of freedom (df) (Î±) 100 â€“ 3 â€“ 1 = 96 ttable is 1.98498. These results indicate Hâ‚€ is rejected and Hâ‚ is accepted because tcount > ttable. Based on the simultaneous significance test, it is known that the value of Fcount 52.744 > Ftable 2.6984 with a value of 0.001 <0.05 there is a simultaneous significant effect of the independent variables on the dependent variable.